Aplikasi Kompos Azolla (Azolla sp.) dan Pupuk Hayati Pada Budidaya Selada (Lactuca sativa L.) Organik - Ida Hodiyah; Darul Zumani; Ade Hilman Juhaeni; Dika Iskandar (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Organic fertilizer plays an essential chemical role such as in providing macro and micro nutrients. One of many plants which is able to be used as organic fertilizer which contains high level of nitrogen for the soil is Azolla pinnata. Biofertilizer is defined as a fertilizer which contains beneficial bacteria which may improve plantâ€™s yield. The aims of this research is to study the application of composted Azolla and M-Bio Biofertilizer on lettuce (Lactuca sativa L.) cultivation. This research was conducted at the research field of Faculty of Agriculture, Siliwangi University by an altitude of 356 m above sea level on August to October 2022. This research was arranged based on Completely Randomized Design in factorial patterns, consisted of two factors. The first factor was the dosage of composted Azolla fertilizer, consisted of three dosages, i.e 10 ton/ha, 15 ton/ha, 20 ton/ha. The second factor was the consentration of M-Bio biofertilizer, consisted of the levels, i.e 10 ml/L, 15 ml/L, 20 ml/L. Each treatment was replicated 3 times, therefore, there were 27 experimental plots. Data were analysed by using the analysis of variance with F test and continued by Duncanâ€™s Multiple Range Test with 5% of critical value. The result of this research shows that there is no interraction between composted Azolla fertilizer and M-Bio consentration on growth and yield of lettuce (Lactuca sativa L.).Â